Kinerja Organisasi Badan Pengelola Keuangan dan Aset Daerah (BPKAD) (Peraturan Daerah Kabupaten Konawe Nomor 4 Tahun 2011) - Hasjad (Jayapangus Press, 2019)
The performance of the Organization of the Regional Financial and Asset Management Agency of Konawe Regency is still lacking in the Management of Regional Assets. The objective conditions of fixed assets and the disorderly recording and reporting of fixed assets are also a problem. This kind of thing can be caused by lack of direction, socialization, and coordination from the Regional Financial and Asset Management Agency of Konawe Regency. Another problem is that there is no regional asset warehouse for securing fixed assets so that fixed assets that are not or have not been exploited are temporarily stored in the backyard of the building, the implication of storing regional property in the backyard of the building is lack of security. The Regional Financial and Asset Management Agency of Konawe Regency also faces constraints related to infrastructure facilities which are still minimal, especially currently in the process of developing an Asset Management Information System (SIM) that requires an increase in adequate infrastructure such as computers, network systems, and other equipment. The minimum number of employees and the low competency of employees or not according to needs is also one of the obstacles in implementing the overall work program.